Globalization of Localized Social Integration: Disembodied ‘Selves’, New Form of Social Interaction and Re-Identification of ‘Who We Are’ in a Virtual Environment - Akter, Tutku (Mediterranean Journal of Social Sciences, 2013)
Social network systems and virtual environment as one of the consequences of the globalization process, and its influences onits users, are discussed in the present study. Some basic concepts, including the necessity of redefining and evenreconceptualizing them, are discussed briefly. This research addresses the facilities as well as the attributes of Facebook as aSocial Network System, and particular features of disembodiment, re-construction, and re-presenting social identities which arealready constructed as a member of small societies. Due to this, â€œWhether â€˜virtual communication environmentsâ€™, â€˜socialnetworksâ€™ are perceived as something like â€˜escape wayâ€™ from socio-cultural restrictions or notâ€ was questioned. For the purposeof the study, an online questionnaire consisting of 55 close-ended questions, with brief information about the purpose and thesignificance of the study, was posted at various FB usersâ€™ profiles. However, only the first 100 volunteer â€˜Turkish Cypriotâ€™ userswere taken as the sample.